Potent induction of wild-type p53-dependent transcription in tumour cells by a synthetic inhibitor of cyclin-dependent kinases - Kotala, V; Uldrijan, S; Horky, M; Trbusek, M; Strnad, M; Vojtesek, B (Cellular and molecular life sciences, 2001)
Activation of the p53 tumour suppressor protein by distinct forms of stress leads to inhibition of cellular proliferation by inducing cell cycle arrest or apoptosis. The cyclin-dependent kinase inhibitor roscovitine has been shown to induce nuclear accumulation of wild-type p53 in human untransformed and tumour-derived cells. We analyzed the response of different human tumour cell lines to roscovitine treatment with respect to their p53 status. Striking induction of wild-type p53 protein and dramatic enhancement of p53-dependent transcription, coinciding with p21WAF1 induction, was observed in wildtype, but not mutant, p53-bearing tumour cells after treatment with roscovitine. The transcriptional activity of p53 was substantially higher in roscovitine-treated cells than in cells irradiated with ultraviolet C or ionizing radiation, even though all these agents induced a similar amount of p53 accumulation. These results highlight the therapeutic potential of roscovitine as an anticancer drug, especially in tumours retaining a functional wild-type p53 pathway.
Keywords: cyklin-dependentní kinasy; buněčné linie; lidé; Cyclin-Dependent Kinases; Purines; roskovitin; fibroblasty; Female; Cell Line; Antineoplastic Agents; Tumor Cells, Cultured; Osteosarcoma; transfekce; Kinetics; nádorové buňky kultivované; protinádorové látky; myši; nádory prsu; Breast Neoplasms; Humans; osteosarkom; kinetika; Melanoma; Mice; Roscovitine; Gene Expression Regulation, Neoplastic; Cyclin-Dependent Kinase Inhibitor p21; genetická transkripce; melanom; zvířata; ženské pohlaví; Cyclins; rekombinantní proteiny; Recombinant Proteins; Tumor Suppressor Protein p53; Animals; Fibroblasts; nádorový supresorový protein p53; regulace genové exprese u nádorů; puriny; Enzyme Inhibitors; Transcription, Genetic; inhibitor p21 cyklin-dependentní kinasy; cykliny; inhibitory enzymů; Transfection